2011
DOI: 10.1080/02640414.2011.553961
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of advanced and intermediate 200-m backstroke swimmers' dominant and non-dominant shoulder entry angles across various swimming speeds

Abstract: During backstroke, an optimum shoulder entry angle of 180° has been anecdotally suggested; however, this has yet to be investigated biomechanically. The aim of this study was to quantify shoulder entry angles for advanced and intermediate backstroke swimmers. Six advanced (season's best <150 s) and six intermediate (season's best >160 s) 200-m backstroke swimmers had markers applied to the medial humeral epicondyles and glenoid cavities. Following a familarization period, participants completed backstroke swim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Our elite swimmers move their upper limbs out of the water more rapidly and have a higher stroke rate, as observed in world-class backstrokers [ 23 ]. Moreover, a better body roll (allowing the hand to glide longer) and an extended second up sweep when finishing the cycle account for higher stroke lengths [ 13 , 34 ]. We observed that the elite swimmers upper limb coordination was more continuous, even if the catch up is the exclusive coordination mode for backstroke (due to the limited shoulder flexibility and the specific body roll [ 18 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our elite swimmers move their upper limbs out of the water more rapidly and have a higher stroke rate, as observed in world-class backstrokers [ 23 ]. Moreover, a better body roll (allowing the hand to glide longer) and an extended second up sweep when finishing the cycle account for higher stroke lengths [ 13 , 34 ]. We observed that the elite swimmers upper limb coordination was more continuous, even if the catch up is the exclusive coordination mode for backstroke (due to the limited shoulder flexibility and the specific body roll [ 18 ]).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the elite swimmers upper limb coordination was more continuous, even if the catch up is the exclusive coordination mode for backstroke (due to the limited shoulder flexibility and the specific body roll [ 18 ]). Thus, swimmers should minimize their upper limb cycle lag time to compensate for the speed loss during the second up sweep [ 23 , 34 ]. Possible reductions in the shoulder entry angle from the suggested optimum may increase resistive drag due to the lateral deviations, but this can be reduced through improvements in technique [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, modern RSFs are typically multifeatured, including underwater treadmills and protruding steps for therapeutic use to improve the versatility of the RSF (25,34). These nonrectangular multifeatured RSFs have been used to assess metabolic work estimation (25,27) and upper-extremity movement (1,24). However, the effects these nonrectangular multifeatured RSFs have on hydrodynamic flow is currently unknown because studies using them have mostly relied on measurements from a single location distance from the projection channel (25,27,33).…”
Section: Introductionmentioning
confidence: 99%
“…In swimming practice, video recordings are used in a variety of ways. They are used for race analysis (software: SwimWatch, SwimOptimum), qualitative technique analysis and quantitative 2D or 3D analysis of kinematic parameters (software: Qualisis, Simi [10][11][12][13][14][15][16][17][18]) of strokes, starts and turns [19]. The use of markers (on body landmarks) is a useful addition to video analysis to obtain quantitative information.…”
Section: Introductionmentioning
confidence: 99%